Device for carrying out batch tail suspension experiment on rodents - CHEN DONGNI; ZHAO YUQI; LI CHONG; LI KEXIN; LIU YINGKUI; LIU YONG; DONG JIAJIA (2023)
The utility model provides a device for carrying out batch tail suspension experiments on rodents. The device comprises a tail suspension frame, a hanging rod, a plurality of roller shutters and experiment units, a hook matched with the hanging rod is fixedly arranged on the tail suspension frame, and the hanging rod is detachably connected to the hook in a hung mode. The multiple roller shutters are arranged in the tail suspension frame in parallel at equal intervals. The bottom of the roller shutter is fixedly connected with the lower portion of the tail suspension frame, and a first buckle is fixedly arranged on the top of the roller shutter and connected with the hanging rod in a clamped mode. The experiment unit is arranged between two adjacent roller shutters; the experiment unit comprises a mouse cage and a mouse tail clamp; the mouse cage is fixedly connected with the tail suspension frame; the mouse tail clamp comprises a mouse tail fixing piece, a sleeve, two symmetrically-arranged long tail clamps